Oxygen Reduction Reaction of Carbon Nanotubes Supported Polypyrrole Doped Toluene Sulfonic Acid in Alkaline Medium - Sri Utami, Rika; Yin Wong, Wai; Herianto Majlan, Edy; Shyuan Loh, Kee (International Journal of Engineering and Technology, 2019)
In this study, polypyrrole/toluene sulfonic acid-based nitrogen doped carbon nanotube (NCNT) is synthesized via chemical oxidative polymerization followed by high-temperature heat treatment under N2 atmosphere. The structure, morphology and composition of the NCNT catalyst are investigated with X-ray diffraction (XRD), scanning electron microscopy (SEM) and Raman spectroscopy. Different N species including pyridinic, pyrrolic, graphitic, and oxidized-N are quantitatively determined by X-ray photoelectron spectroscopy (XPS). The electrocatalytic activity of NCNT towards oxygen reduction reaction (ORR) in alkaline condition is evaluated with cyclic voltammetry (CV) and rotating disk electrode (RDE). The globular and tubular structure of NCNT can be clearly seen from SEM images. The typical Raman spectrum for NCNT showed two prominent bands around 1348 cm-1 (D band) and 1568 cm-1 (G band). High-resolution XPS spectrum of N 1s for NCNT showed that graphitic-N has the highest percentage (39.36%), whereas the pyridinic-N (26.54%), pyrrolic-N (18.88%) and oxidized-N (15.22%). The ORR electrocatalytic activity of the NCNT in 0.1 M KOH has the onset potential of -0.154 V vs. Ag/AgCl, the current density 0.455 mA/cm2, and electron transfer number of n â‰ˆ 4.Â Â